(untitled) (Strojniški vestnik – Journal of Mechanical Engineering, 2023)
This study proposes a reliability-based optimization framework for improving manufacturing process performance. Statistical analysis and simulation methods were applied to investigate the relationship between process parameters and product quality. The results show that optimized parameter selection significantly reduces production errors and improves manufacturing reliability.